2021
DOI: 10.3390/molecules26051221
|View full text |Cite
|
Sign up to set email alerts
|

Compact NMR Spectroscopy for Low-Cost Identification and Quantification of PVC Plasticizers

Abstract: Polyvinyl chloride (PVC), one of the most important polymer materials nowadays, has a large variety of formulations through the addition of various plasticizers to meet the property requirements of the different fields of applications. Routine analytical methods able to identify plasticizers and quantify their amount inside a PVC product with a high analysis throughput would promote an improved understanding of their impact on the macroscopic properties and the possible health and environmental risks associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The presence of phthalates may be due to additives added to plastics as plasticizers or small molecules. Furthermore, the aromatic signal around 7 ppm for microplastics (S2) can be used to differentiate types of plasticizers such as diisononyl cyclohexane-1,2-dicarboxylate (DINCH) from others such as diethylhexyl phthalate and diisobutyl phthalates as described by Duchowny and Adams (2021). Of particular interest, plasticizers constitute about one third of polymer additives (Rahman, 2004) and global demand for plasticizers is expected to increase from $78.91 billion in 2020 to $87.81 billion in 2021 according to a recent report (Researchandmarkets.com).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of phthalates may be due to additives added to plastics as plasticizers or small molecules. Furthermore, the aromatic signal around 7 ppm for microplastics (S2) can be used to differentiate types of plasticizers such as diisononyl cyclohexane-1,2-dicarboxylate (DINCH) from others such as diethylhexyl phthalate and diisobutyl phthalates as described by Duchowny and Adams (2021). Of particular interest, plasticizers constitute about one third of polymer additives (Rahman, 2004) and global demand for plasticizers is expected to increase from $78.91 billion in 2020 to $87.81 billion in 2021 according to a recent report (Researchandmarkets.com).…”
Section: Discussionmentioning
confidence: 99%
“…92, 130.43 ppm and 8.13, 129.46 ppm, 4.28,67.75 ppm and 4.18, 67.27 ppm, 1.21, 23.12 ppm to 1.29,23.92 ppm, 1.51, 38.91 ppm to 1.59, 38.91 ppm, and 0.82, 10.87 ppm suggesting presence of phthalates. Duchowny and Adams (2021) reported the 1 H NMR spectra of various plasticizers. The aromatic peaks were observed in the region approx., 7 ppm, the α-CH2 groups next to the ester bond (3 to 4 ppm), aliphatic CH2 (around 1 ppm) and the CH3 chain ends around 0.8 ppm consistent with the general structure of phthalates derived from phthalic anhydrides.…”
Section: Microplastic Polymer Types and Abundance In Surface Watermentioning
confidence: 99%
“…However, as high-field NMR spectroscopy is difficult to operate in industrial sites, there is a demand for benchtop NMR spectrometers to be used as routine equipment for quality control. Recently, several studies have confirmed that benchtop NMR spectroscopy has the potential to directly verify materials in industrial sites lacking advanced measurement facilities [48,49]. A benchtop NMR spectrometer was used for the quantitative molecular characterization of polystyrene-containing polymer blends and block copolymers [50].…”
Section: Polymer Materialsmentioning
confidence: 99%
“…Benchtop NMR spectroscopy can be used for the analysis of organic additives in polymers. In a recent study, plasticizers in PVC were quantitatively analyzed using a 40 MHz 1 H NMR spectrometer [48,53]. To lower the cost of analysis, NMR spectra were obtained using non-deuterated n-hexane as a solvent, as its signals minimally overlapped with those of the plasticizers.…”
Section: Polymer Materialsmentioning
confidence: 99%
See 1 more Smart Citation